Gambaran Pengetahuan Ibu Rumah Tangga tentang Tanda dan Gejala Infeksi HIV/AIDS Wilayah Haji Ungar RT.001/RW.III Kelurahan Tanjung Ayun Sakti Kecamatan Bukit Bestari Tanjungpinang 2014 - Dewi Pusparianda; Dede Dwika Wamardhana (STIKes Patria Husada Blitar, 2015)
The number HIV incident in Tanjungpinang keep rising in 2013, the rising of the incident reach to 244 cases (the rising occurring to 42% in 2012). Some groups think the infection of HIV/AIDS is obtained by prostitute, homosexual, and so on. The infection also obtained by housewife and children. In early research, showed that 3 housewife didnâ€™t know the signs and symptomps of the infection. Itâ€™s a basic to do a research â€Overview of housewife knowledges about signs and symptomps infection of HIV/AIDS in district Haji Ungar RT.001/RW.III Kelurahan Tanjung Ayun Sakti Kecamatan Bukit Bestari Tanjungpinangâ€. The purpose of this research was to know the overview of housewife knowledge about signs and symptomps of HIV/AIDS in district Haji Ungar RT. 001/RW. III Kelurahan Tanjung Ayun Sakti Kecamatan Bukit Bestari Tanjungpinang. The study was done in 12 June 2014. The Number of samples of this research was 30 housewives. The Sample technique in this research was randomize. The instrument used in this research was questionaire. The result Obtained that the housewife knowledges in districk Haji Ungar RT. 001/RW. III against the signs of the symptomps infection HIV/AIDS in district Haji Ungar RT. 001/RW. III Kelurahan Tanjung Ayun Sakti Kecamatan Bukit Bestari was great (86%). Housewife knowledges was great, maybe its because of good introduction about that problem. Level of education, experience, or good socio-cultural towards it will make housewife can recognize the problems. It was recommended that the housewife could get more knowledge and health expecially about body resistance. Housewife also recommended to do health checking in public health services.